A novel file system supporting rich file classification. (October 2022) - Albadri, Nehad; Dekeyser, Stijn
Abstract: Existing implementations of file systems often seem to be made on an ad hoc and implicit basis. This paper aims to enhance the organization of files and retrieval of files by modifying the traditional hierarchical file system to improve built-in query support and bulk metadata updates supported at the file system level. We introduce tags in a hierarchy of file collections and use links to allow file retrieval from multiple paths as files exist in multiple directories simultaneously. By using a series of modest changes to the hierarchical file system, we propose a novel Linked Tree Tags (LTTs) model. These changes include using multiple tags instead of names, collections instead of directories, exposing a query language at the Application Programming Interface (API) level, and allowing controlled file links. We assess our model's expressive capability and demonstrate that LTTs overcome traditional file systems' limits and provide users with the to manage their files easily.